2016
DOI: 10.1158/1078-0432.ccr-16-0392
|View full text |Cite
|
Sign up to set email alerts
|

Density, Distribution, and Composition of Immune Infiltrates Correlate with Survival in Merkel Cell Carcinoma

Abstract: Purpose Merkel cell carcinoma (MCC) is an aggressive cancer with frequent metastasis and death with few effective therapies. Because programmed death ligand-1 (PD-L1) is frequently expressed in MCC, immune checkpoint blockade has been leveraged as treatment for metastatic disease. There is therefore a critical need to understand the relationships between MCPyV status, immune profiles, and patient outcomes. Experimental Design IHC for CD3, CD8, PD-1, PD-L1, and MCPyV T-antigen (to determine MCPyV status) was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 43 publications
7
91
0
5
Order By: Relevance
“…Histologische Charakteristika mit einer prognostischen Bedeutung sind die Tumordicke und die An-bzw. Abwesenheit von tumorinfiltrierenden Lymphozyten, insbesondere CD8 + -T-Zellen [26][27][28]. Die Wertigkeit des histologischen Subtyps (trabekulär, kleinzellig, intermediär) sowie des molekularbiologischen oder immunhistochemischen Nachweises des Merkelzellpolyomavirus für die Abschätzung der Prognose wird aktuell noch kontrovers diskutiert [29,30].…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Histologische Charakteristika mit einer prognostischen Bedeutung sind die Tumordicke und die An-bzw. Abwesenheit von tumorinfiltrierenden Lymphozyten, insbesondere CD8 + -T-Zellen [26][27][28]. Die Wertigkeit des histologischen Subtyps (trabekulär, kleinzellig, intermediär) sowie des molekularbiologischen oder immunhistochemischen Nachweises des Merkelzellpolyomavirus für die Abschätzung der Prognose wird aktuell noch kontrovers diskutiert [29,30].…”
Section: Resultsunclassified
“…Retrospective studies have shown the following clinical features to be associated with an unfavorable prognosis: advanced tumor stage, male gender, primary tumor in the head/neck region or on the trunk, and immunosuppression. Histological characteristics of prognostic significance include tumor thickness and the presence or absence of tumor‐infiltrating lymphocytes, especially CD8 + T cells . The prognostic significance of the histological subtype (trabecular, small‐cell, intermediate) and the molecular or immunohistochemical detection of the Merkel cell polyomavirus continues to be the subject of controversial debate .…”
Section: Introductionmentioning
confidence: 99%
“…The total area of tissue containing inflammatory cells was designated by a dermatopathologist and IHC cells were quantified using Aperio image scope. The percentage of positive cells and H‐Score (intensity of staining [1+, 2+, 3+] x % of positive cells with that staining intensity for each marker were recorded by digital image analysis, as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Histologische Charakteristika mit einer prognostischen Bedeutung sind die Tumordicke und die An‐ bzw. Abwesenheit von tumorinfiltrierenden Lymphozyten, insbesondere CD8 + ‐T‐Zellen . Die Wertigkeit des histologischen Subtyps (trabekulär, kleinzellig, intermediär) sowie des molekularbiologischen oder immunhistochemischen Nachweises des Merkelzellpolyomavirus für die Abschätzung der Prognose wird aktuell noch kontrovers diskutiert .…”
Section: Allgemeinesunclassified